Adsorbents based on natural polymers for removal of some heavy metals from aqueous solution - Ahmed Fawzy El-Kafrawy; Shimaa Mohamed El-Saeed; Reem Kamel Farag; Hend Al-Aidy El-Saied; Manar El-Sayed Abdel-Raouf (Egyptian Journal of Petroleum)
Heavy metal ions are discharged into water from several industries. They are carcinogenic and they cause severe environmental hazards. In the present work the ability of removal of copper and lead from aqueous solutions has been studied using carboxy methyl β cyclodextrin, poly(ethylene glycol) β cyclodextrin and their magnetic counterparts. Effects of pH, concentration of the metal ion, temperature and contact time have been studied. Equilibrium isotherms for the adsorption of the metals were measured experimentally. Results were analysed at different temperatures and the characteristic parameters for each adsorption isotherm were determined. The adsorption process has been found exothermic in nature and thermodynamic parameters, Gibb’s free energy (ΔG), change in enthalpy (ΔH) and change in entropy (ΔS) have been calculated. The paper also includes results on the kinetic measurements of adsorption of the metal on modified β cyclodextrin and their magnetic nano composites at different temperatures. It was found that poly (ethylene glycol) β cyclodextrin showed better performance than carboxy methyl β cyclodextrin.